Barriers to Implementing Just in Time (JIT) Inventory Management Among Coffee Shop MSMEs in Jember Regency - Muhsyi, Abdul; Khusna, Khanifatul; Sukarno, Hari (Ilomata International Journal of Management, 2026)
This study explores the implementation of the Just in Time (JIT) inventory system in coffee shop MSMEs in Jember Regency, East Java, which is renowned as a coffee production center. Facing intense competition from major brands, local coffee shops must optimize inventory management to maintain sustainability. Using a descriptive qualitative approach, data were collected from 14 local coffee shops through in-depth interviews and participant observation. The findings reveal that while some MSMEs have adopted JIT, most face significant obstacles, such as inconsistent coffee quality, fluctuating raw material prices, supplier reliability, and high storage and transportation costs. These constraints hinder comprehensive JIT adoption and may impact operational efficiency. The study suggests that careful supplier selection, effective stock planning, and quality monitoring are essential to overcoming JIT barriers and ensuring sustainable business operations. The findings have practical implications for MSME inventory management and local economic development.